Mapping Research Trends in Reproductive Health Among Female Adolescents: A Bibliometric Analysis Using Dimensions.Ai and Vosviewer - Choirunissa, Risza; Nugraheni, Sri Achadi; Purnami, Cahya Tri; Wahyuningsih, Nur Endah (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2024)
Reproductive health and positive mental health are crucial components of adolescent girls' overall well-being, deeply interconnected and influenced by social, economic, and environmental factors. Adolescent girls face unique challenges in managing both reproductive and mental health, impacted by societal pressures, limited access to health education, and disparities in healthcare. This study aims to analyze trends, themes, and patterns in the literature related to reproductive health and positive mental health among female adolescents, using bibliometric methods to identify key focus areas, research gaps, and influential studies published between 2019 and 2024. This bibliometric analysis followed a simplified PRISMA approach involving identification, screening, and inclusion stages. An initial search identified 1,015 articles on reproductive health and positive mental health in adolescent girls (2020-2024). After abstract and title screening, 856 articles were included. Data analysis using VOSviewer allowed for the visualization of bibliometric networks, highlighting key themes and citation patterns. The analysis revealed that reproductive health education, resilience, and mental well-being are central themes, with stress and social relationships significantly influencing health behaviors. The COVID-19 pandemic exacerbated challenges in accessing services, while digital solutions emerged as promising interventions. This study emphasizes the importance of integrated approaches to reproductive and mental health, providing a basis for future research and policy development to support adolescent girls' well-being.